Hubungan layanan perpustakaan sekolah dengan minat baca peserta didik di SMAN 4 Kota Tangerang Selatan - Rahman, Aditiya; Lolytasari, Lolytasari; Munawwaroh, Zahrotul (Daluang: Journal of Library and Information Science, 2023)
Introduction. Providing school library services to increase students' interest in reading is still an important study for school libraries. Increasing reading interest in the SMAN 4 Tangerang Selatan Library is carried out by providing collaborative services to improve scientific communication. This research needs to be carried out so that the services provided by the library can accommodate all students in reading interest services and become basic research for school libraries in the South Tangerang area.Methodology. This study uses a quantitative approach, with a correlation coefficient test to answer the hypothesis. The population is 346 students, so a sample of 186 respondents is obtained using a simple random sampling technique. Questionnaires were distributed to 186 students with Likert scale scores with four alternative answers and documentation studies to complete data collection.Results and Discussion. This study found a relationship between library services and students' reading interest, as evidenced by the contribution of 24.6% between library services and students' reading interest. In comparison, the remaining 75.4% was explained by other variables not examined. The tendency of library services to increase reading interest is still in the moderate category.Conclusion. This study describes the school's efforts to increase student's interest in reading with the strength of the services provided by the library. Reading skills need to be trained so that the more the library can provide the facilities needed for reading, the more trained students will be.